Internalisasi Konsep Tri Rahayu sebagai Upaya Pencegahan Bullying di Sekolah - Nur Kholiq, Yusuf; Maesyaroh, Wulan; insani, Nur Hanifah (PAKAR Pendidikan, 2024)
Bullying This is a serious problem that must be prevented immediately. One effort to prevent bullying is to internalize the Tri Rahayu concept. This research aims to 1) describe the Tri Rahayu concept as a prevention effort bullying, 2) analyze the relevance of the Tri Rahayu concept as a prevention effort bullying at school. This research uses a qualitative approach with a library study method. Data collection techniques were carried out using documentation techniques. This research data is in the form of information regarding prevention bullying and the Tri Rahayu concept. The source of the literature study in this research is journal articles accessed via google scholar. The data analysis technique in this research uses content analysis techniques, while the data wetness technique uses theoretical triangulation. The research results show that there are several attitudes that can be internalized in the Tri Rahayu concept as a prevention effort bullying. This attitude is introspective, tepa slira, aja dumeh, srawung, tulung tinulung, eling, waspada, lan tumindak alus sarwi aris, and obey the law. The Tri Rahayu concept is very relevant to prevention efforts bullying in schools because this concept teaches kindness and peace towards oneself, fellow humans and the nation. The results of this research provide a new concept regarding prevention efforts bullying through the philosophical concept of Ki Hadjar Dewantara which can be used as a reference and prevention guide bullying at school